2015
DOI: 10.1159/000375397
|View full text |Cite
|
Sign up to set email alerts
|

Post Stroke Pain: Identification, Assessment, and Therapy

Abstract: Background: Pain is a common complication after stroke and is associated with the presence of depression, cognitive dysfunction, and impaired quality of life. It remains underdiagnosed and undertreated, despite evidence that effective treatment of pain may improve function and quality of life. Summary: We provide an overview of the means for clinical assessment and risk factors for the development of post-stroke pain, then review the newest available literature regarding the commonest post-stroke pain syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
182
3
31

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(242 citation statements)
references
References 110 publications
(162 reference statements)
12
182
3
31
Order By: Relevance
“…It has also been shown that quality of life is very poor in patients that have a combination of different types of pain (27). In some studies (14,28,29), it has been reported that there is no significant relationship in health-related quality of life between stroke survivors with chronic pain and those without chronic pain. This report is different from the results of the present study where a significant relationship was observed in healthrelated quality of life between stroke survivors with and without chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that quality of life is very poor in patients that have a combination of different types of pain (27). In some studies (14,28,29), it has been reported that there is no significant relationship in health-related quality of life between stroke survivors with chronic pain and those without chronic pain. This report is different from the results of the present study where a significant relationship was observed in healthrelated quality of life between stroke survivors with and without chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…The reported prevalence of PSP varies, depending on several factors such as study design, definition and classification of pain and characteristics of the participants enrolled in the studies. According to a previous survey, PSP was disclosed by 49.3% of chronic post-stroke patients [1][2][3]. Symptoms in the upper extremity of the affected side in post-stroke patients often have more than one etiology.…”
Section: Introductionmentioning
confidence: 99%
“…These make accurate diagnosis and appropriate management challenging for clinicians [1,2]. The presence of pain is associated with cognitive decline, increased functional dependence [4], fatigue [5], depressed mood, and impaired health-related quality of life [6].…”
Section: Introductionmentioning
confidence: 99%
“…1). Имеющиеся в литературе данные позволяют предположить, что лече-ние боли ассоциировано с улучшением когнитивных функций, качества жизни и повседневного функциониро-вания пациента [13].…”
Section: Introductionunclassified
“…Имеются данные о повышении эффективно-сти реабилитационных мероприятий и улучшении реа-билитационного прогноза у пациентов в зависимости от адекватности и времени начала терапии ПБС [13].…”
Section: Introductionunclassified